The Universal declaration of Human rights and the modern Asian values - Chu, Hong Thanh (Đại học Quốc gia Hà Nội, 2020)
In 1948, the United Nations General Assembly solemnly adopted the Universal Declaration of Human Rights (UDHR). The UDHR is still valid until the present day and looks forward to the future, which is the foundation for the formation of the International Bill of Human Rights, including two basic human rights conventions adopted by the United Nations in1966. Although there are still a number of different opinions, but it is undeniable that the great historical stature of the UDHR, is the goal, motivation, endless inspiration for the protection and promotion of rights and basic human freedom worldwide. Since then there have been many statements, regional and intergovernmental charter, the Constitution of the nations have been born and UDHR references. The Cultural, democratic, humanitarian and human rights values in Asian countries cannot be influenced by the UDHR. There have been many studies on Asian values associated with the UDHR’s influence on the policies and laws of countries in this region. This article is about the UDHR and modern Asian values with the desire to contribute more deeply to this relationship in a rapidly changing world with new opportunities and challenges.